Using co-creating mass-customisation and innovation climate for enhanced value: Empirical investigation in international modular jewellery market. Issue 1 (11th June 2019) - Adel, Heba Mohamed; Younis, Raghda Abulsaoud Ahmed
Abstract : Purpose: This paper aims to study the impact of innovation climate (IC) on co-creating modular mass-customisation (CMMC) in terms of cost effectiveness, volume effectiveness, responsiveness, product modularity and collaborative assembly. Additionally, this research paper investigates the effect of IC and CMMC on the value to customer (VC) in a modular jewellery emerging market that includes international companies. Design/methodology/approach: After conducting a comprehensive literature review, the authors suggested a conceptual framework and examined it using mixed methods approach. In addition to qualitative focus groups, questionnaires were filled – across five-point Likert scale format – through 63 depth interviews carried out with subject-matter-experts working at 14 international organisations in the Egyptian modular jewellery market. SmartPLS software was used for structural equation modelling analysis. Findings: Results showed that CMMC positively and significantly affects VC. Furthermore, IC positively and significantly affects both CMMC and VC. Practical implications: Recent industrial developments that can be observed in such international modular jewellery sector can be enhanced by the empirical evidence of this research regarding the importance of developing IC for more creative manufacturing approach of modular mass-customisation and better VC. Originality/value: To the best of our knowledge, it is the first empirical study that investigates the relationship between CMMC, IC and VC in a unique jewellery market, which recently generated high customer involvement in the assembly/reassembly processes. Conceptually and empirically, it consolidates and adds to the literature of production and operations management (mass-customisation), organisational studies and innovation science (organisational climate for innovation) and applied social sciences.